2016
DOI: 10.1016/j.ajoc.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Ozurdex completely located inside a crystallized lens - Results of 14 months

Abstract: PurposeTo report the therapeutic efficacy and results of an accidentally injected intralenticular sustained-release dexamethasone implant (Ozurdex) in a patient with macular edema secondary to central retinal vein occlusion at 14 months after injection.ObservationsWe present a 70-year-old female patient with central retinal vein occlusion who underwent an Ozurdex injection. Patient discontinued from the treatment period during the 14-month and there was no ophthalmologic examination of the patient. Detailed op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 5 publications
(8 reference statements)
1
17
0
1
Order By: Relevance
“…Poornachandra et al [11] and Clemente-Tomás et al [3] have reported no acceleration of cataract progression. Many authors [3, 4, 7, 10, 11] have found a gradual resolution of the macular edema with an intralenticular implant but Baskan et al [12] found decreasing vision and no edema improvement. Coca-Robinot et al [9] have observed very little effect of the intralenticular implant on the macular edema.…”
Section: Discussionmentioning
confidence: 99%
“…Poornachandra et al [11] and Clemente-Tomás et al [3] have reported no acceleration of cataract progression. Many authors [3, 4, 7, 10, 11] have found a gradual resolution of the macular edema with an intralenticular implant but Baskan et al [12] found decreasing vision and no edema improvement. Coca-Robinot et al [9] have observed very little effect of the intralenticular implant on the macular edema.…”
Section: Discussionmentioning
confidence: 99%
“…These four cases were all caused by intravitreal injection of dexamethasone into the crystalline lens[6-8]. In recent years, with the increase in Ozurdex injections, cases of iatrogenic lens injury have increased[9-11]. Due to the special suspending property of TA, the complication caused by TA implanted into the crystalline lens is unique.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] found the intralenticular implant to still be effective with a gradual resolution of the macular edema, Baskan et al . [ 7 ] reported no such improvement at all with further deterioration of vision.…”
Section: Discussionmentioning
confidence: 99%